2018
DOI: 10.1210/jc.2018-01067
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Homeostasis and Energy Balance in Children With Pseudohypoparathyroidism

Abstract: In contrast to other monogenic obesity syndromes, our results support reduced energy expenditure, not severe hyperphagia, as the primary cause of abnormal weight gain in PHP. Patients with PHP are at high risk for dysglycemia without reduced insulin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…Patients with PHP1A or PHP1B develop early-onset obesity, usually within the first 2 years of life; this may be the first and only symptom in many patients until the diagnosis is established during adolescence or adulthood [3, 4, 67, 68]. Several mechanisms may contribute to excessive acquisition and maintenance of fat mass, including a defect in the Gsα-dependent melanocortin signaling pathway (possibly responsible for the patients’ hyperphagic trait [68, 69]), decreased resting energy expenditure compared to obese controls [68, 70, 71], low sympathetic nervous system activity, decreased lipolysis [72], and GH-releasing hormone resistance in the pituitary [73, 74]. Overall, we now know that obesity or overweight is associated with all types of PHP and related disorders [22], with the exception of POH, PPHP, and osteoma cutis [3, 52, 57, 75, 76].…”
Section: Obesitymentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with PHP1A or PHP1B develop early-onset obesity, usually within the first 2 years of life; this may be the first and only symptom in many patients until the diagnosis is established during adolescence or adulthood [3, 4, 67, 68]. Several mechanisms may contribute to excessive acquisition and maintenance of fat mass, including a defect in the Gsα-dependent melanocortin signaling pathway (possibly responsible for the patients’ hyperphagic trait [68, 69]), decreased resting energy expenditure compared to obese controls [68, 70, 71], low sympathetic nervous system activity, decreased lipolysis [72], and GH-releasing hormone resistance in the pituitary [73, 74]. Overall, we now know that obesity or overweight is associated with all types of PHP and related disorders [22], with the exception of POH, PPHP, and osteoma cutis [3, 52, 57, 75, 76].…”
Section: Obesitymentioning
confidence: 99%
“…Postprandial hyperglycemia is common in children with PHP1A and PHP1B [71]. The lipid profile is not profoundly affected in PHP1A patients [69, 80]. Hypertension was reported in 1 study of PHP [81], yet the incidence of cardiovascular diseases was not increased in cohort studies conducted in Denmark [41, 80].…”
Section: Metabolic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Early-onset obesity was also significant. Morbid obesity without evidence of hyperphagia was identified [2,50], and it was discovered that the cause of rapid weight gain in childhood was not hyperphagia but rather a decrease in resting energy expenditure (REE) [51,52,53 ▪ ]. In adults with PHP1A, there are higher rates of type 2 diabetes and reduced insulin sensitivity compared with obese controls [54].…”
Section: Differences Between Pseudohypoparathyroidism Type 1a and Psementioning
confidence: 99%
“…However, it was recently reported that children with PHP1A are at a high risk for dysglycaemia without reduced insulin sensitivity and have lower HgbA1c levels than controls. Interestingly, these children seem to have an increased sucrose preference as well [53 ▪ ].…”
Section: Differences Between Pseudohypoparathyroidism Type 1a and Psementioning
confidence: 99%